Some applications of the Rice, Rampsperger, Kassel and Marcus theory on unimolecular reactions in the gas phase - Engelbrecht, W. J.(Willem Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1969.